The constitution of algorithms : ground-truthing, programming, formulating - Jaton, Florian author. (Cambridge, Massachusetts : The MIT Press, 2020)
"Ethnographic study of the constitution of algorithms"-- Studying computer scientists -- A first case study -- Von Neumann's draft, electronic brains, and cognition -- A second case study -- Mathematics as a science -- A third case study. "Ethnographic study of the constitution of algorithms"--